Does Green Brazilian Propolis Extract Improve Functional Capacity in Symptomatic Chronic Coronary Disease?—A Pilot Randomized Trial - Clara Salles Figueiredo; Luiz Carlos Santana Passos; Caio Rebouças Fonseca Cafezeiro; Rodrigo Morel Vieira de Melo; Tainá Teixeira Viana; Eduardo Jorge Gomes de Oliveira; Andresa Aparecida Berretta; Marcelo Augusto Duarte Silveira (Pharmaceuticals)
Background: Inflammation plays a critical role in the progression of coronary heart disease (CHD). Low-dose colchicine has shown promise in reducing cardiovascular events, and green Brazilian propolis extract (EPP-AF® (standardized Brazilian green propolis extract) was provided by Apis Flora Indl. Coml. Ltda, Ribeirão Preto, SP, Brazil), known for its anti-inflammatory properties, may offer additional therapeutic benefits. This pilot study aimed to evaluate whether six weeks of EPP-AF® supplementation improves functional capacity assessed by treadmill exercise testing. Methods: This was a randomized, double-blind, placebo-controlled pilot study conducted at a coronary disease clinic in Brazil. Patients aged ≥ 18 years with stable CHD receiving optimized medical therapy were randomized in a 2:1 ratio to receive either 200 mg of EPP-AF® or placebo twice daily for six weeks. The primary outcome was the change in treadmill exercise duration (in seconds). Secondary outcomes included total exercise time, functional capacity (measured in metabolic equivalents of task [METs]), high-sensitivity C-reactive protein (hs-CRP) levels, the Seattle Angina Questionnaire (SAQ), and the Canadian Cardiovascular Society (CCS) angina classification. Statistical analysis was performed on an intention-to-treat basis. Results: A total of 59 patients were randomized, with a median follow-up of 6.5 weeks. There was no significant difference in the primary endpoint between groups: the median change in treadmill test time was 39 s in the EPP-AF® group versus 30 s in the placebo group (p = 0.83). No improvements were observed in METs, hs-CRP levels, SAQ scores, or CCS class in the EPP-AF® group. No major adverse cardiovascular events occurred during the study. Conclusions: EPP-AF® did not improve functional capacity, inflammatory markers, or angina symptoms in patients with stable CHD compared to placebo.